2014
DOI: 10.1128/genomea.01081-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Two Ulvan-Degrading Isolates, Strains LTR and LOR, That Belong to the Alteromonas Genus

Abstract: Here, we report the draft genome sequence of two ulvan-degrading Alteromonas spp. isolated from the feces of the sea slug, Aplysia. These sequenced genomes display a unique ulvan degradation machinery compared with ulvanolytic enzymes previously identified in Nonlabens ulvanivorans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…LTR, and Pseudoalteromonas sp. PLSV, (8,12,13). Genome annotation was manually confirmed by CAZy 4 and revealed that these strains encoded many polysaccharide-degrading enzymes.…”
Section: Table 2 Primers Used In This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…LTR, and Pseudoalteromonas sp. PLSV, (8,12,13). Genome annotation was manually confirmed by CAZy 4 and revealed that these strains encoded many polysaccharide-degrading enzymes.…”
Section: Table 2 Primers Used In This Studymentioning
confidence: 99%
“…LTR, and Pseudoalteromonas sp. PLSV (12,13). Inspection of the genomes did not reveal genes encoding proteins homologous to N. ulvanivorans ulvan lyase.…”
mentioning
confidence: 96%
“…This draft genome, along with the additional draft sequences of N. ulvanivorans ( 10 ) and two Alteromonas spp. ( 14 ), will allow a better understanding of the utilization and exploitation of the Ulvales biomass. A BLAST search of the known ulvan lyase and the GH105 against the draft genome has found no matching sequences.…”
Section: Genome Announcementmentioning
confidence: 99%
“…These draft genome sequences of ulvan-utilizing bacteria, along with the already (9), Alteromonas spp. (10), and a Pseudoalteromonas sp. (11), will open up possibilities for the usefulness of polysaccharide ulvan from Ulva spp.…”
mentioning
confidence: 99%